LEGAL PROTECTION FOR CONSUMERS AGAINST SKINCARE PRODUCTS WITHOUT MARKETING PERMITS THAT ARE SOLD FREELY - Imelda Mardayanti (RADJA PUBLIKA, 2024)
This research aims to find out how legal protection is for consumers regarding skincare products without distribution permits that are sold freely. This research focuses on examining the application of the rules/norms in positive law, which is then connected to the problems discussed in this research. Using a statutory approach method (state approach). The data collection method used in the research is document study as the first step in legal research. The results of this research show that this research concluded that consumers who experience losses as a result of consumer rights being violated by business actors can take legal action. Implementation of Law no. 8 of 1999 concerning Consumer Protection has not been optimal in providing compensation to consumers who are harmed by products from business actors. Consumers who experience losses due to legal violations committed by business actors can take legal action against them through litigation or non-litigation. Consumers have the right to obtain safety from goods/services that must not be dangerous if consumed so that consumers are not harmed both physically and spiritually.